Blepharoplasty with a Buried Double Twisted Suture Technique to Correct Upper Eyelid Epiblepharon. Issue 4 (April 2016) - Choi, Seung Woo; Goldberg, Robert A.; Lew, Helen
Abstract : Background: The authors evaluated the clinical efficacy of blepharoplasty using a newly developed, buried double twisted suture (BDTS) technique to correct upper eyelid epiblepharon. Methods: This retrospective study was conducted from October 2013 to July 2015 at the Oculoplastic Clinic, Bundang CHA Medical Center, CHA University, Seongnam, Korea. A total of 122 eyes from 61 patients with upper eyelid epiblepharon were enrolled. Blepharoplasty with a BDTS technique was performed on all eyes, followed by evaluation of clinical outcomes and complications. After surgery, success was defined as the persistence of a double eyelid and the upper eyelid eyelashes not touching the cornea under slit lamp examination. Results: The 61 patients were composed of 29 females and 32 males. The average age was 9.0 ± 7.7 years, and the average follow-up period was 7.3 ± 5.2 months. After surgery, the margin reflex distance increased from 2.0 ± 1.0 to 3.2 ± 0.9 mm ( P < 0.05). The success rate was 98.1%. Epiblepharon recurred in 1 patient (1.9%) and was treated after 2 months. Knot exposure was a postoperative complication in 2 patients (3.8%). The knots were buried in the deep layer under local anesthesia. Overall, all cases showed good results without complications. Conclusions: Blepharoplasty with a BDTS technique is relatively simple and effective for correction of epiblepharon with a low rate of complications. This technique can be applied to double eyelid surgery based on the excellent cosmetic outcomes.